The influence of bisphenol A on the human body - Kozioł, Magdalena; Krasa, Aleksandra; Łopuszyńska, Anna Małgorzata; Pawlicki, Mateusz; Piekarska, Ewa; Piecewicz-Szczęsna, Halina; Wójcik, Anna (Journal of Education, Health and Sport, 2021)
Introduction: Bisphenol A (BPA) is a substance commonly used in industry for the production of everyday plastic products. It is also found in thermal paper. Global pollution of the environment by BPA results in constant exposure to its harmful effects. This substance penetrates the skin, respiratory tract and food into the body. BPA, due to its structure similar to estrogens, disturbs e.g. functioning of the endocrine system and increases the risk of certain cancers. Material and methods: The PubMed and Google Scholar databases were used to review the literature. Description of knowledge: Exposure of breast cancer cells to BPA results in increased aromatase synthesis and increased proliferation of ER + cells. Moreover, BPA stimulates the growth of neoplastic breast cancer cells not only at high doses but also at low doses (<25 µg / kg / day). This substance has an affinity for the estrogen receptor. Daily doses of BPA have been found to increase the density of the mammary gland in mammography. Exposure of this substance to human prostate epithelial cells induced the potential of cancer development in prostate cells. Recent studies have shown that BPA causes increased bronchial reactivity and reduced epidermal regeneration capacity, which proves its pro-inflammatory effect. Research proves that BPA reduces the ability to learn and disrupts the Glu / GABA neurotransmitter ratio. Conclusions: The ubiquitous presence of BPA has a negative effect on living organisms. By accumulating in adipose tissue, it exposes us to constant exposure, which is dangerous even in low doses. Increases the risk of infertility and cancer. Acting pro-inflammatory, it increases the susceptibility to allergens. There are calls for the use of BPA-free packaging and for steps to be taken to reduce BPA production. Key words: bisphenol A; BPA; estrogen; mechanisms; receptors; cancer.